Inferior Turbinate classification system, grades 1 to 4: Development and validation study. (12th September 2014) - Camacho, Macario; Zaghi, Soroush; Certal, Victor; Abdullatif, Jose; Means, Casey; Acevedo, Jason; Liu, Stanley; Brietzke, Scott E.; Kushida, Clete A.; Capasso, Robson
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To develop a validated inferior turbinate grading scale. Study Design Development and validation study. Methods Phase 1 development (alpha test) consisted of a proposal of 10 different inferior turbinate grading scales (>1, 000 clinic patients). Phase 2 validation (beta test) utilized 10 providers grading 27 standardized endoscopic photos of inferior turbinates using two different classification systems. Phase 3 validation (pilot study) consisted of 100 live consecutive clinic patients (n = 200 inferior turbinates) who were each prospectively graded by 18 different combinations of two independent raters, and grading was repeated by each of the same two raters, two separate times for each patient. Results In the development phase, 25% (grades 1–4) and 33% (grades 1–4) were the most useful systems. In the validation phase, the 25% classification system was found to be the best balance between potential clinical utility and ability to grade; the photo grading demonstrated a Cohen's kappa (κ) = 0.4671 ± 0.0082 (moderate inter‐rater agreement). Live‐patient grading with the 25% classification system demonstrated an overall inter‐rater reliability of 71.5% (95% confidence interval [CI]: 64.8–77.3), with overall substantial agreement (κ = 0.704 ± 0.028). Intrarater reliability was 91.5% (95% CI: 88.7–94.3). Distribution for the 200 inferior turbinates was as follows: 25% quartile = grade 1, 50% quartile (median) = grade 2, 75% quartile = grade 3, and 90% quartile = grade 4. Mean turbinate size was 2.22 (95% CI: 2.07‐2.34; standard deviation 1.02). Categorical κ was as follows: grade 1, 0.8541 ± 0.0289; grade 2, 0.7310 ± 0.0289; grade 3, 0.6997 ± 0.0289, and grade 4, 0.7760 ± 0.0289. Conclusions The 25% (grades 1–4) inferior turbinate classification system is a validated grading scale with high intrarater and inter‐rater reliability. This system can facilitate future research by tracking the effect of interventions on inferior turbinates. Level of Evidence 2c Laryngoscope, 125:296–302, 2015